The impact of parent-targeted eHealth educational interventions on infant procedural pain management: a systematic review protocol. (August 2019) - Richardson, Brianna; Benoit, Britney; Rutledge, Kallen; Dol, Justine; Misener, Ruth Martin; Latimer, Margot; Smit, Michael; McGrath, Patrick; Campbell-Yeo, Marsha
ABSTRACT: Objective: The objective of this review is to determine if electronic health (eHealth) educational interventions for infant procedural pain and pain management impact parental outcomes (mental health outcomes, knowledge utilization outcomes, and parental involvement in care outcomes) and infant outcomes (morbidity outcomes, pain outcomes, health system outcomes). Introduction: Pain in infants is a common concern for parents. Routine postpartum care for infants in early life requires them to endure painful procedures, yet infants often receive little to no pain management. While research has shown that parents can reduce their infant's pain during procedures by breastfeeding or skin-to-skin contact, parents may not be aware of their role in pain management. Despite the recent rapid increase in eHealth resources to educate parents about infant pain management, their impact has yet to be evaluated. Inclusion criteria: This review will consider studies that include eHealth educational interventions targeted at parents during pregnancy and up to one year postpartum. All experimental study designs will be included. Primary outcomes will include: parental stress and anxiety, self-efficacy, knowledge, attitudes, eHealth intervention usage, acceptance of eHealth intervention, involvement in pain management, and infant pain response. Methods: PubMed, CINAHL, PsycINFO, Embase, Scopus, Web of Science, and SciELO will be searched for studies published in English. Critical appraisal and data extraction will be conducted by two independent reviewers using standardized tools. Quantitative data, where possible, will be pooled in statistical meta-analysis, or if statistical pooling is not possible, the findings will be reported narratively.